2020
DOI: 10.1044/2019_jslhr-l-19-0213
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of Computer-Adaptive Alternate Short Forms for the Assessment of Anomia Severity

Abstract: Purpose The purpose of this study was to verify the equivalence of 2 alternate test forms with nonoverlapping content generated by an item response theory (IRT)–based computer-adaptive test (CAT). The Philadelphia Naming Test (PNT; Roach, Schwartz, Martin, Grewal, & Brecher, 1996)was utilized as an item bank in a prospective, independent sample of persons with aphasia. Method Two alternate CAT short forms of the PNT were administered to a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We then quantified the agreement between the 30-item PNT-CT and a variable-length CT-generated form of the PNT, called CT-VL, in a follow-up study. 46 The CT-VL was configured to avoid presenting overlapping items from the 30-item PNT-CT administration for a given patient. In addition, for the CT-VL, a stopping rule was set as precision equal to or lower than that obtained by the 30-item PNT-CT.…”
Section: Developing More Efficient and Flexible Testsmentioning
confidence: 99%
“…We then quantified the agreement between the 30-item PNT-CT and a variable-length CT-generated form of the PNT, called CT-VL, in a follow-up study. 46 The CT-VL was configured to avoid presenting overlapping items from the 30-item PNT-CT administration for a given patient. In addition, for the CT-VL, a stopping rule was set as precision equal to or lower than that obtained by the 30-item PNT-CT.…”
Section: Developing More Efficient and Flexible Testsmentioning
confidence: 99%
“…For example, object naming performance by persons with chronic aphasia tends to be very stable over time 58,70,71 and in contrast to these results for the ACOM, IRT-based estimates of measurement error in naming have agreed reasonably well with estimates obtained from test-retest differences. 72,73 It may also be useful in this context to draw a distinction between change scores that exceed measurement error and change scores that exceed those normally found in an untreated sample of individuals. 74 In any case, it is currently recommended that users of the ACOM be cautious in using the SEs provided by the software output when making inferences about change scores for individuals because they may underestimate measurement error due to instability over time.…”
Section: Recommendations For Interpretation Of Acom Change Scoresmentioning
confidence: 99%
“…Specifically, Fergadiotis, Hula, Swiderski, Lei, and Kellough ( 2019) demonstrated that scores on the PNT -CAT from 47 PWA were in high agreement with their scores on the full PNT. In addition, Hula et al (2020) developed two equivalent, dynamic, test forms with non-overlapping items for repeated administrations.…”
Section: Computerized Adaptive Version Of the Philadelphia Naming Testmentioning
confidence: 99%
“…Further, currently available tests invalidly assume constant measurement error based on which 95% confidence intervals are estimated around ability scores. With the exception of recent work (e.g., Hula et al, 2020) on the PNT, naming tests assume equal measurement error regardless of ability level. This ignores that measurement error varies as a function of the degree to which the difficulty of the test targets the ability level of the person being tested (Embretson & Reise, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation